Risk factors for in-hospital death in elderly patients over 65 years of age with dementia: A retrospective cross-sectional study. Issue 26 (30th June 2022) - Meng, Zhangmin; Cheng, Linan; Hu, Xiuying; Chen, Qian
Abstract : As the population continues to age, dementia is becoming a huge social, economic, and healthcare burden. However, the risk factors for in-hospital death in elderly patients over 65 years of age with dementia are not well understood. Identifying factors that affect their prognosis could help clinicians with scientific decision-making. To examine the risk factors for in-hospital death in elderly patients over 65 years of age with dementia in the Geriatric Department of West China Hospital. In this retrospective, cross-sectional study, we analyzed inpatients aged ≥65 years with dementia between 2010 and 2016 using electronic medical records from the Information Center of West China Hospital. The risk factors for death were assessed using multivariable logistic regression. Out of a total of 2986 inpatients with dementia, 3.4% died. Patient deaths were related to digestive diseases, respiratory diseases, circulatory diseases, urinary diseases, and chronic obstructive pulmonary disease, whereas patient survival was associated with osteoporosis and Parkinson disease. Patients with a mean length of hospital stay of ≥60 days had an increased risk of death (all P <.05). In the multiple logistic regression analysis, age ≥80 years, digestive diseases, respiratory diseases, urinary diseases, diabetes, chronic obstructive pulmonary disease, and ≥7 comorbidities were risk factors for death. Mortality in hospitalized older patients with dementia is low, but some risk factors may be easily ignored. These findings could raise awareness among clinicians and caregivers about risk factors in hospitalized older patients, particularly hospitalized elderly patients with multiple comorbidities. Therefore, to reduce mortality, early prevention and management of potential risks are necessary.